The Relevance of Abu Bakar Atjeh's Concept of Tazkiyah al-Nafs in Addressing Mental Health Issues - Ihwan Agustono; Nur Hadi Ihsan; Fahmi Habibi Musthofa (DINIKA : Academic Journal of Islamic Studies, 2024)
Mental health issues in today’s world are a major concern that must be addressed. Tazkiyah al-nafs emerges as a significant answer to the problem in this context. Tazkiyah al-nafs is primarily concerned with purifying the soul, cleansing the heart of desire and greed, and bringing one closer to Allah. Abu Bakar Atjeh, a well-known Indonesian scholar, believes that tazkiyah al-nafs is one of the most effective medications for people suffering from mental health conditions. Hence, this article aims to explore the concept of tazkiyah al-nafs by Abu Bakar Atjeh and its relevance in addressing mental health problems. This study is library research with a qualitative approach. Data was obtained using documentation techniques, and the collected data was analyzed using descriptive analysis methods. The research concludes that there are two ways to achieve mental health through the tazkiyah al-nafs method, namely khalwah and żikr. The conclusion in this paper is that tazkiyah al-nafs has a positive and comprehensive impact because of its holistic and spiritual-based approach so that these concepts of khalwah and żikr in tazkiyah al-nafs can be applied to various mental health problems.